ABCB1 and ABCC4 efflux transporters are involved in methyl parathion detoxification in ZFL cells. Issue 1 (February 2015) - Nornberg, Bruna Félix; Batista, Carolina Reyes; Almeida, Daniela Volcan; Trindade, Gilma Santos; Marins, Luis Fernando
Highlights The MXR mechanism is activated to detoxify from methyl parathion. The toxic effects of MP on ZFL cells were increased in the presence of the efflux transporter inhibitor. The combined exposure to MP and the inhibitor caused an increase in gene expression of P-gp1 (Abcb1) and MRP4 (Abcc4).